Strengthening of Wood-Like Materials via Densification and Nanoparticle Intercalation - David Novel; Simone Ghio; Andrea Gaiardo; Antonino Picciotto; Vincenzo Guidi; Giorgio Speranza; Maurizio Boscardin; Pierluigi Bellutti; Nicola M. Pugno (Nanomaterials, 2020)
Recently, several chemical and physical treatments were developed to improve different properties of wood. Such treatments are applicable to many types of cellulose-based materials. Densification leads the group in terms of mechanical results and comprises a chemical treatment followed by a thermo-compression stage. First, chemicals selectively etch the matrix of lignin and hemicellulose. Then, thermo-compression increases the packing density of cellulose microfibrils boosting mechanical performance. In this paper, in comparison with the state-of-the-art for wood treatments we introduce an additional nano-reinforcemeent on densified giant reed to further improve the mechanical performance. The modified nanocomposite materials are stiffer, stronger, tougher and show higher fire resistance. After the addition of nanoparticles, no relevant structural modification is induced as they are located in the gaps between cellulose microfibrils. Their peculiar positioning could increase the interfacial adhesion energy and improve the stress transfer between cellulose microfibrils. The presented process stands as a viable solution to introduce nanoparticles as new functionalities into cellulose-based natural materials.